Modelling the physical properties change of canned glutinous rice porridge during cooking. Issue 10 (13th February 2019) - Wang, Lei; Wang, Mengting; Lv, Ruiling; Guo, Mingming; Ye, Xingqian; Ding, Tian; Liu, Donghong
Abstract : The changes in the physical properties of rice porridge during cooking in a sealed can were investigated and modeled systematically. Abstract : In this study, we modeled the water absorption, softening and shear viscosity change kinetics of canned rice porridge during cooking as well as estimated the thermodynamic properties involved in hydration. Moreover, the internal microstructure of rice kernels was observed under different hydrothermal conditions. During cooking, the water absorption and shear viscosity alteration rate increased with temperature, whereas the softening rate decreased. However, the temperature did not significantly affect the equilibrium value of the physical properties. The variation tendencies of the moisture content and hardness of the kernels could be expressed satisfactorily by the exponential and the generalized exponential models. The porridge shear viscosity variations fitted the sigmoidal and its generalized models. Thermodynamic parameters (enthalpy, entropy and Gibbs free energy) revealed that the hydration process was non-spontaneous and exothermic. Furthermore, scanning electron microscopy images and the results of the X-ray diffraction analysis showed the microstructure of the kernels during cooking, and the kernels formed a homogeneous mesh structure at earlier times during the initial stage at higher temperatures. These findings would provide valuable information for the optimization of canned rice porridge production.